2021
DOI: 10.1007/s00415-021-10667-7
|View full text |Cite
|
Sign up to set email alerts
|

Paradigm shift in acute dizziness: is caloric testing obsolete?

Abstract: Objective Cold and warm water ear irrigation, also known as bithermal caloric testing, has been considered for over 100 years the ‘Gold Standard’ for the detection of peripheral vestibular hypofunction. Its discovery was awarded a Nobel Prize. We aimed to investigate the diagnostic accuracy of Caloric Testing when compared to the video head impulse test (vHIT) in differentiating between vestibular neuritis and vestibular strokes in acute dizziness. Design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…The vHIT is able to evaluate the function of the VOR on high-frequency head thrust. Traditional vestibular tests, such as the caloric test and the rotatory chair, may be rendered obsolete by vHIT, as suggested by Morrison et al (2022) [ 17 ]. Aside from that, the purpose of using healthy people is to monitor the typical changes in a physiological state that are brought on by the administration of drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The vHIT is able to evaluate the function of the VOR on high-frequency head thrust. Traditional vestibular tests, such as the caloric test and the rotatory chair, may be rendered obsolete by vHIT, as suggested by Morrison et al (2022) [ 17 ]. Aside from that, the purpose of using healthy people is to monitor the typical changes in a physiological state that are brought on by the administration of drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Our results of VOR gain accuracy are similar to older studies ( 8 ). The known dissociation between caloric test results and vHIT might affect the overall specificity of this test ( 6 ). A recent study showed a slight worsening of accuracy of AI for stroke classification based on HINTS data ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…A subset of VOR gain data presented here have been published elsewhere (6,(18)(19)(20)(21). A neurootologist with 2 years' experience in the field, performed physical examination, Caloric Testing, and vHIT testing in all enrolled patients.…”
Section: Vhit Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the proposed protocols or algorithms for the evaluation of AVS have included caloric testing, although a unilateral weakness to caloric stimuli could significantly impact differential diagnosis 13 . On the other hand, in the presence of spontaneous nystagmus, classic bithermal tests may be difficult to interpret and may not be recommended 13 , 14 . The main purpose of this study is to evaluate the possibility of detecting a pathological unilateral weakness in the presence of spontaneous nystagmus using only a caloric cold test (ice water test) 15 and to recommend the use of this procedure in the differential diagnosis of APV from central nervous system (CNS) diseases that may present as an isolated vertigo.…”
Section: Introductionmentioning
confidence: 99%